Moonstruck - Jewison, Norman, 1926-2024.; Palmer, Patrick; Shanley, John Patrick; Cher, 1946-; Cage, Nicolas, 1965-; Gardenia, Vincent; Dukakis, Olympia; Aiello, Danny, 1933-2019.; MGM Home Entertainment Incorporated; Metro-Goldwyn-Mayer. (Santa Monica, California : MGM Home Entertainment, 1998)
An "unlucky in love" Italian-American widow just weeks away from her wedding falls for her fiance's younger brother.
Standard full screen format (modified to fit TV screen).
Videodisc release of 1987 motion picture.
Special features include audio commentary by Cher, Norman Jewison and John Patrick Shanley; original theatrical trailer.
Cher, Nicolas Cage, Vincent Gardenia, Olympia Dukakis, Danny Aiello.
Rated PG.
DVD, Dolby digital.
Keywords: Man-woman relationships -- Drama; Comedy films; Films for hard of hearing people; Feature films; Videos (DVD)